Automated non-destructive (NDT) technique based on the alternating current field measurement (ACFM) - Zhou, Jiannong. (2008)
This thesis reports on the development of an automated NDT inspection PC system. The system is based on an ACFM Crack Microgauge Model U10, a Kawasaki JS-5 manipulator and a Microsoft Windows equipped personal computer which executes the software developed by the author. An ACFM pencil-probe, carried by the manipulator, is moved over the structures to be examined. The crack Microgauge measures the magnetic field intensity value. The application software is used to control and communicate with the crack Microgauge and the manipulator, analyse ACFM the data, and detect cracks.